Metal assisted self-assembled rod like nanostructures for effective cellular internalization. Issue 16 (4th April 2018) - Bhattacharya, Sourav; Mukherjee, Saikat; Das Sarma, Jayasri; Shunmugam, Raja
Abstract : This work describes a metal assisted self-assembled rod like nanostructure which can be used for the delivery of therapeutic agents. Abstract : Well-designed polymeric self-assembled materials are in high demand because of the need for better alternatives to the conventional system. A nano-structure that is self-assembled, driven by different forces related to synthetic polymers follows different uptake kinetics at the cellular level. Herein we designed a norbornene-functionalized amphiphilic homopolymer that represents a unique self-assembled nanostructure in polar solvent. The self-assembled nanoaggregates were scrutinized using dynamic light scattering (DLS), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) techniques. The vesicular nanoaggregates of the homopolymer changed their shape to nanorods in the presence of Fe(ii ) in polar medium. The self-assembled nanorods we reutilized for doxorubicin loading showed a higher uptake than the vesicular structures loaded with the drug in the absence of Fe(ii ). This simple strategy of preparing nanorods can be helpful for future application in the field of drug delivery.